Impact of change in air temperature on the biological parameters of larvae and productivity of silkworm cocoons - Boboyev Yusuf; Bekkamov Chorshanbi; Nurmanova Salomat; Aminbayeva Nigora (BIO Web of Conferences, 2023)
Especially, the construction of special silkworm rooms near the mulberry yards, which are organized for harvesting mulberry silkworms several times a year, gives positive results. “…construction of special facilities for silkworm breeding, increasing the planting of mulberry seedlings on the edges of the farm, intensively continuing the activities aimed at ensuring the employment of the population due to the effective use of existing opportunities” are defined as urgent tasks. For this purpose, it is necessary to ensure that the area of rooms and special silkworm rooms selected for silkworm rearing by the silkworm rearing units of the homesteaders and farms involved in silkworm rearing is adequate, and when the silkworms pass from age to age, they should be thinned out, fertilized, and provided with sufficient quality feed. Summing up on the basis of the analyzed data, it is worth noting that during the period of silkworm rearing, full feeding of larvae during their youth, moderate air temperature in the silkworm room, smooth development of silkworms without becoming large and small, and vitality by ensuring that the biological indicators of the mulberry silkworm are high and the activity of the silk-secreting glands is increased, the productivity and yield characteristics of the cultivated silkworm cocoons are achieved.